2012
DOI: 10.1093/cercor/bhs090
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Processing of Voice Gender Studied Using a Continuous Carryover fMRI Design

Abstract: Normal listeners effortlessly determine a person's gender by voice, but the cerebral mechanisms underlying this ability remain unclear. Here, we demonstrate 2 stages of cerebral processing during voice gender categorization. Using voice morphing along with an adaptation-optimized functional magnetic resonance imaging design, we found that secondary auditory cortex including the anterior part of the temporal voice areas in the right hemisphere responded primarily to acoustical distance with the previously heard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 52 publications
8
55
1
1
Order By: Relevance
“…Humans easily recognize different voices, and this ability is of considerable social importance. Voice-selective areas have been demonstrated in the human brain (Belin, Zattorre, & Ahad, 2002;Belin, Zattorre, Lafaille, Ahad, & Pike, 2000), localized bilaterally along the upper bank (middle and anterior) of the Superior Temporal Sulcus (STS) (Alho et al, 2006;Belin, et al, 2002), and also in the inferior and orbitofrontal cortex (Charest, Pernet, Latinus, Crabbe, & Belin, 2012;Fecteau, Armony, Joanete, & Belin 2005) as well as surrounding insular cortex (Johnstone, van Reekum, Oakes, & Davidson, 2006;Rama et al, 2004). This neural selectivity for voice has also been established in other mammals, in particular primates (Johnstone et al, 2006;Rama et al, 2004) and more recently dogs (Andics, Gacsi, Farago, Kis, & Miklosi, 2014).…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Humans easily recognize different voices, and this ability is of considerable social importance. Voice-selective areas have been demonstrated in the human brain (Belin, Zattorre, & Ahad, 2002;Belin, Zattorre, Lafaille, Ahad, & Pike, 2000), localized bilaterally along the upper bank (middle and anterior) of the Superior Temporal Sulcus (STS) (Alho et al, 2006;Belin, et al, 2002), and also in the inferior and orbitofrontal cortex (Charest, Pernet, Latinus, Crabbe, & Belin, 2012;Fecteau, Armony, Joanete, & Belin 2005) as well as surrounding insular cortex (Johnstone, van Reekum, Oakes, & Davidson, 2006;Rama et al, 2004). This neural selectivity for voice has also been established in other mammals, in particular primates (Johnstone et al, 2006;Rama et al, 2004) and more recently dogs (Andics, Gacsi, Farago, Kis, & Miklosi, 2014).…”
Section: Introductionmentioning
confidence: 84%
“…Based on functional MRI (Belin, et al, 2002(Belin, et al, , 2000Charest et al, 2012) and Transcranial Magnetic Stimulation (Bestelemeyer, et al, 2011) results observed in healthy volunteers, we hypothesized that patients with right fronto-temporal stroke will show a deficit in gender categorization but intact phonological performances. Our results using both a qualitative (classification of percentage of responses) and a quantitative (signal detection theory) approach confirmed this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations